Load curtailment minimization by optimal placements of SVC/STATCOM. (16th September 2014) - Govind Singh, Jai; Guha Thakurta, Priyanko; Soder, Lennart
Summary: In this paper, a new sensitivity‐based methodology has been proposed for optimal placement of a static VAr compensator (SVC)/static synchronous compensator (STATCOM) to minimize load curtailment that is required to ensure system security, integrity and reliability after undesirable changes occur in the system. SVC/STATCOM has a significant impact on control of reactive power and thereby system bus voltages. This motivated to develop an appropriate approach to find their optimal location in order to accomplish the above said objective. The suggested sensitivity factors have been defined as the rate of change in load curtailment with respect to the change in SVC/STATCOM control settings. To investigate the effectiveness of the proposed methodology an optimal power flow problem has been formulated with an objective to minimize the load curtailment and is tested on IEEE 14‐bus and practical 75‐bus Indian systems. It is observed from the obtained results that the required load curtailment drastically reduced with the placement of SVC/STATCOM, along with improvement in system voltage profile at various operating conditions. This methodology can be used to limit the amount of load curtailment, thereby reducing lost revenue, outage cost, customer's service interruption and possibly civil unrest in some areas. Copyright © 2014 John Wiley & Sons, Ltd.